2D g-C3N4–MnO2 nanocomposite for sensitive and rapid turn-on fluorescence detection of H2O2 and glucose. Issue 42 (17th October 2018) - Zhou, Yu-Jie; Li, Li; Wan, Yuan-Hui; Chen, Ting-Ting; Chu, Xia
Abstract : 2D g-C3 N4 –MnO2 nanocomposite for sensitive and rapid turn-on fluorescence detection of H2 O2 and glucose. Abstract : The accurate determination and quantification of H2 O2 and glucose are necessary for diagnosis and bioengineering. Herein, we have reported a novel method for the rapid and selective detection of H2 O2 and glucose using g-C3 N4 –MnO2 nanocomposite. In this method, the fluorescence of graphitic-C3 N4 (g-C3 N4 ) was quenched by MnO2, which was attributed to fluorescence resonance energy transfer (FRET) between g-C3 N4 nanosheets and the deposited MnO2 . When H2 O2 was introduced, the MnO2 was reduced to Mn 2+, which led to the elimination of FRET and the recovery of the quenched fluorescence. This H2 O2 detection system was also suitable for glucose detection since H2 O2 is one of the main products in the oxidation reaction of glucose catalyzed by glucose oxidase. Therefore, our method has a great application prospect in diabetes research and clinical diagnosis. Additionally, the fluorescence was linear with the concentration of H2 O2 in the range of 0 to 130 μM, with the detection limit of 1.5 μM, and also showed a good linear relationship with glucose in the range of 0 to 150 μM, with the detection limit of 1.5 μM. In addition to a wide linear response, the proposed sensor showed advantageous characteristics, such as easy preparation, low cost, high selectivity, rapid detection, and turn-on fluorescence response. Therefore, our proposed strategy would provide a new general strategy to develop low-cost, sensitive biological and clinical diagnostic methods.